2014
DOI: 10.1021/nl500926y
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and Highly Curved Model Membranes on Vertical Nanowire Arrays

Abstract: Sensing and manipulating living cells using vertical nanowire devices requires a complete understanding of cell behavior on these substrates. Changes in cell function and phenotype are often triggered by events taking place at the plasma membrane, the properties of which are influenced by local curvature. The nanowire topography can therefore be expected to greatly affect the cell membrane, emphasizing the importance of studying membranes on vertical nanowire arrays. Here, we used supported phospholipid bilaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 47 publications
(67 reference statements)
2
35
0
Order By: Relevance
“…Recent results have highlighted how high‐aspect‐ratio nanostructures can result in protein recruitment, alter the dynamics of membrane‐embedded proteins, and cause complex interactions with cytoskeletal elements, but a precise understanding of these mechanics is still lacking. Both modeling and experimental results hint at a complex relationship between the molecular interactions of the cell membrane with the sharp features and porosity of high‐aspect‐ratio nanostructures, e.g., Dabkowska et al used supported lipid bilayers on nanowire substrates to experimentally explore this interface, their results suggesting that curvature influences protein localization . Further understanding of the molecular nature of this interface would provide valuable insight.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results have highlighted how high‐aspect‐ratio nanostructures can result in protein recruitment, alter the dynamics of membrane‐embedded proteins, and cause complex interactions with cytoskeletal elements, but a precise understanding of these mechanics is still lacking. Both modeling and experimental results hint at a complex relationship between the molecular interactions of the cell membrane with the sharp features and porosity of high‐aspect‐ratio nanostructures, e.g., Dabkowska et al used supported lipid bilayers on nanowire substrates to experimentally explore this interface, their results suggesting that curvature influences protein localization . Further understanding of the molecular nature of this interface would provide valuable insight.…”
Section: Discussionmentioning
confidence: 99%
“…Performing FRAP on substrates with denser nanowires also shows full fluorescence recovery, however the recovery is slower (data not shown), suggesting that the bilayer conforms to the nanofeatures of the array as in the case of bilayers on SiO x -coated nanowires. 26 Since it is not always feasible to produce nanostructures on a substrate using epitaxy in order to verify the presence of a bilayer, we have investigated whether nanostructured surfaces obtained by depositing nanoparticles on the substrate can be used to verify the presence of a bilayer. This would then enable the visualization of the lipid fluorescence and recovery and hence the assessment of the presence of a bilayer on the substrate without costly and complicated sample preparation.…”
Section: Nanoscale Communicationmentioning
confidence: 99%
“…[18][19][20][21][22] This feature has also been exploited for the integration of biomolecules with nano-objects. [23][24][25][26] Therefore, SLB formation on new materials is a key step to enable the assessment of the materials in terms of bio-applications. SLB formation can be assessed using e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to obtain surface layers with nanostructure beyond flat bilayers that mimic the curvature of membranes observed in nature is by using a nanostructured template as a substrate. Recently, we showed that fluid supported bilayers can be formed on vertical nanowire forests from vesicles in solution [9]. The bilayers follow the contours of the nanowires to form continuous and locally highly curved model membranes to which proteins and vesicles can be attached.…”
Section: Introductionmentioning
confidence: 99%